RALYL increases hepatocellular carcinoma stemness by sustaining the mRNA stability of TGF-β2 - Wang, Xia; Wang, Jin; Tsui, Yu-Man; Shi, Chaoran; Wang, Ying; Zhang, Xin; Yan, Qian; Chen, Miao; Jiang, Chen; Yuan, Yun-Fei; Wong, Chun-Ming; Liu, Ming; et al. (Nature communications, 2021)
Growing evidences suggest that cancer stem cells exhibit many molecular characteristics and phenotypes similar to their ancestral progenitor cells. In the present study, human embryonic stem cells are induced to differentiate into hepatocytes along hepatic lineages to mimic liver development in vitro. A liver progenitor specific gene, RALY RNA binding protein like ( RALYL ), is identified. RALYL expression is associated with poor prognosis, poor differentiation, and metastasis in clinical HCC patients. Functional studies reveal that RALYL could promote HCC tumorigenicity, self-renewal, chemoresistance, and metastasis. Moreover, molecular mechanism studies show that RALYL could upregulate TGF-β2 mRNA stability by decreasing N6-methyladenosine (m 6 A) modification. TGF-β signaling and the subsequent PI3K/AKT and STAT3 pathways, upregulated by RALYL, contribute to the enhancement of HCC stemness. Collectively, RALYL is a liver progenitor specific gene and regulates HCC stemness by sustaining TGF-β2 mRNA stability. These findings may inspire precise therapeutic strategies for HCC. RALYL is a liver progenitor cell-specific gene but its role in hepatocellular carcinoma (HCC) remains unknown. Here, the authors demonstrate that RALYL regulates HCC stemness through upregulation of TGF-β2 mRNA stability by decreasing N6-methyladenosine modification.